PEMAKSIMALAN PROFIT PERTANIAN MELALUI PROGRAM LINEAR : STUDI KASUS PADA PERTANIAN PADI DAN JAGUNG DI KELURAHAN TARA-TARA, KOTA TOMOHON - Christari Lois Palit; Alycia Nikita Poluan; Breisi Maria Luntungan; Meyni Novela Runtu; Miranda Yuliana Sondakh; Tesalonika Junira Mogi; Virginia Sarah Kaparang (SOSCIED, 2025)
Farmers in Tara-Tara Village, Tomohon City, still face difficulties in increasing their income due to limited production inputs, such as land, fertilizer, pesticides, and seeds. Decision-making based solely on experience often leads to inappropriate resource utilization. This study aims to determine the most profitable combination of rice and corn planting areas while still taking into account the limitations of available inputs. A quantitative approach based on Linear Programming was used in the analysis, with data collected through interviews and field observations. Calculations were performed using the Simplex method using QM for Windows software. The results showed that the optimal allocation was obtained at a planting area of ??0.97 units for rice and 1.53 units for corn, resulting in an estimated profit of Rp 12,615,150 per planting season. From the analysis of slack variables, it was found that fertilizer and seeds were the most limiting constraints on increasing production, while land still has room for utilization. Based on these findings, this study recommends that farmers continue to focus their efforts on rice and corn commodities and increase the availability of fertilizer to fully optimize the land